PEMANFAATAN PRASASTI TURYYAN SEBAGAI SUMBER PEMBELAJARAN SEJARAH SMA - Pi'i, Pi'i (Universitas Negeri Malang, 2020)
One of the obstacles in historical learning is the unskilled and inexperienced history teacher in selecting/arranging and wrapping the appropriate learning sources. This is due to the effects of an ineffective learning process in which expository strategy is the primary roled model besides the self-student given assignments. To handle the problems, history teachers are supposed to observe and to use the historical heritages found around the residence. In this case, Turyyan epigraph is the historical learning source. The Learning source is designed following the IT based learning development, like making learning videos. Thus, the learners are boosted to an exciting history learning environment system. Moreover, the learners will also receive beneficial informations, knowledge, and life skill learning experiences.